Effect of Hemodynamic Changes During Percutaneous Mitral Balloon Valvuloplasty on Short and Long Term Clinical Outcome - Akurk, Erdal; Kurtoglu, Ertugrul; Eyupkoca, Ferhat; ERMİŞ, NECİP; Acikgoz, NUSRET; AÇIKGÖZ, NUSRET; Yagmur, Julide; CANSEL, MEHMET; Altuntas, Mehmet Sait; PEKDEMİR, HASAN (My University, 2012)
Aims: We aim of this study is to determine whether hemodynamic changes that occur before and after percutaneous mitral balloon valvuloplasty (PMV) procedure is a predictor in determining the short- and long-term clinical results in patients with mitral stenosis (MS).